Capital Exchange between Islamic Boarding Schools and Political Parties in the 2019 Election - Siti Kholifah (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2020)
This study examines the social practices of Islamic boarding schools in Jombang in the 2019 elections. It aims to analyze the role and capital exchange between Islamic boarding schools in Jombang and political parties. This study is important because the intersection of Islamic boarding schools and politics has been going on since colonial times until now. The political dynamics of Islamic boarding schools cannot be separated from NU because several NU Kiai are in the vortex of local and national politics. In the 2019 presidential election, a Kiai of NU named Kiai Ma’ruf Amin ran as Jokowi’s partner to be a vice president. As a place for the establishment of NU, Islamic boarding schools in Jombang have a magnet in gaining votes both in the legislative and presidential elections in 2019. By using Pierre ’Bourdieu’s theory as an analytical tool, this research conducted a case study approach. Data collection techniques carried out through interviews, observation, and documentation. The informants are determined purposively. The results of this study indicate that the exchange of capital between Islamic boarding schools and political parties is dominated by symbolic capital exchanges of Islamic boarding schools with the social capital of political elites and political parties. The blue bloodline of Islamic boarding schools and seniority of a Kiai or Nyai have an essential role in determining the reproductive strategy and capital exchange with political parties. Also, the dominance of social practices carried out in Islamic boarding schools. The power of symbolic capital and social capital of NU Islamic boarding school became a tool for conducting bargaining positions with elite political parties, including presidential and vice-presidential candidates. In the end, the capital exchange between Islamic boarding schools and political parties became obvious in getting votes in the 2019 elections.